Effects of improved content knowledge on pedagogical content knowledge and student performance in physical education. (2nd January 2017) - Iserbyt, Peter; Ward, Phillip; Li, Weidong
Abstract : Background : Pedagogical content knowledge (PCK) is an interaction of several knowledge bases upon which the teacher makes decisions about what and how to teach. To date, there are no studies in physical education directly documenting relationships between specialized content knowledge (SCK) and PCK. Such relationships have not been empirically evidenced, in part because there have not been operational and thus replicable measures of SCK and PCK. SCK is the knowledge teachers need to teach content to students and consists of knowledge of errors and task presentations. In this study we used measures of SCK and PCK that were operational, replicable, and quantifiable. Purpose : In this study we examined changes in PCK and concomitant changes in student performance as a function of a content knowledge workshop designed to teach teachers predominately SCK in badminton. Play Practice served as the instructional model for badminton. Our research questions were: (1) How did the teacher's enacted PCK differed after the content knowledge workshop? and (2) How did student performance defined in terms of correct and incorrect trials differed as a function of teacher's PCK? Methods : A teacher taught a six-day badminton unit to four intact classes (comparison), participated in a content knowledge workshop, and then taught a six-day badminton unit to four different classes (experimental). Eight students in each class blocked into low, average, and high skilled students ( n  = 64) were observed. Our quasi-experimental design used treatment, class nested within conditions, skill levels, and interactions among conditions, gender, and skill levels. Results : The results showed that the teacher's PCK was substantively different before and after the workshop. Higher counts of descriptions, analogies/metaphors, cues, and specific congruent feedback were observed in the experimental classes compared to the comparison classes. Higher counts of correct demonstrations and lower counts of partially correct demonstrations were observed in the experimental groups compared to the comparison. In the experimental classes, the teacher selected 80 tasks that were developmentally and principle (i.e. in accordance with Play Practice) appropriate compared to 12 in the control. Student performance was also significantly different. Participants in the experimental group performed a higher percentage of correct trials and less incorrect trials relative to those in the comparison group. Students from all skill levels in the experimental groups performed significantly better than those in the comparison groups. Discussion and conclusion : This study demonstrates that improved SCK changes PCK and student performance. The changes in the teacher's PCK from comparison groups to the experimental classes differed in two areas: how tasks were presented and the appropriateness of the tasks selected for student performance. The use of a knowledge packet-CK workshop in professional development for both pre-service and in-service teachers requires further investigation in terms of the content and organization of the knowledge packets and in terms of developing packets for other physical education content areas besides badminton.